2012
DOI: 10.5152/akd.2012.150
|View full text |Cite
|
Sign up to set email alerts
|

The degree of premature hair graying as an independent risk marker for coronary artery disease: a predictor of biological age rather than chronological age

Abstract: The degree of premature hair graying as an independent risk marker for coronary artery disease: a predictor of biological age rather than chronological ageKoroner arter hastalığı için bağımsız bir risk öngörücüsü olarak saçın erken beyazlama düzeyi: Zamansal yaştan çok biyolojik yaşın öngörücüsü ABSTRACTObjective: Age is the most important and uncorrectable coronary risk factor at the moment. The concept of measuring aging biologically rather than only chronologically may be of importance in clinical practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 26 publications
4
57
1
1
Order By: Relevance
“…One of the earliest clinical signs which may possibly help in recognizing early onset of CAD in a young smoker is the presence of premature graying of hair. Although this sign was described as early as in 80's by Eisentein et al (5,6) and later few studies from our centre have also shown similar results (7,8), it has become a subject of intense research only very recently in the western world (9).…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…One of the earliest clinical signs which may possibly help in recognizing early onset of CAD in a young smoker is the presence of premature graying of hair. Although this sign was described as early as in 80's by Eisentein et al (5,6) and later few studies from our centre have also shown similar results (7,8), it has become a subject of intense research only very recently in the western world (9).…”
Section: Introductionmentioning
confidence: 48%
“…In addition, hair-graying intensity was also associated with age, hyperlipidemia and family history of CAD and creatinine levels (9).…”
Section: Figure 1: a 42 Years Old Man Chronic Smoker And Suffered Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of self-esteem and worries over a possibility of worse underlying metabolic conditions such as diabetes cholesterolemia, coronary artery disease and osteopenia affected a huge number of the participants. Several studies have reported results that indicate a putative association between PHG and other hidden ill-health conditions [1,11,18,19] whereas other findings have disputed this view [9,17]. This equivocal hypothesis of PHG as ill-health indicator calls for the need of more studies in order to devise possible preventative approaches if a positive association is firmly established.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reports different patterns of onset with men's first onset involving the temporal and occipital regions while women's initial onset involving the frontal region. In the quest to describe the occurrence of PHG, Jo and co-workers [10] proposed a numerical grading of five grades I to V at a 20% interval scale referring to 20, 40, 60, 80 and 100% of grayness while other studies have proposed a much more nominal grading of 1-5 representing pure black, predominantly black, equal black and white, predominantly white and pure white respectively [11]. Globally, PHG is on the rise and it has been shown to affect up to over 50% of the young people [8,10].…”
Section: Introductionmentioning
confidence: 99%